Desain Sistem Informasi Manajemen Data Pelanggaran Perda di Satpol PP Dumai sebagai Implementasi Internal e-Government - Albadri, Aldhi; Azmi, Khairul; Sya'bani, Muhammad Agung (Sekolah Tinggi Teknologi Dumai, 2025)
The enforcement of local regulations (perda) in Dumai City has faced administrative challenges due to the continued use of inefficient manual data recording systems. This study aims to design a management information system for recording violations of local regulations at the Civil Service Police Unit (Satpol PP) as part of an internal e-Government implementation. The system development method follows an iterative approach, beginning with needs analysis through observation and interviews, system design using Unified Modeling Language (UML), and implementation using the Laravel framework and MySQL database. The developed system includes key features such as violation and advertisement data input forms, category management, graphical report visualization, and printing of report. Testing results show that the system significantly improves data recording efficiency, accelerates historical data retrieval, and enhances report accuracy. Performance evaluation indicates up to a 70% increase in efficiency compared to manual methods. Therefore, the system contributes to digital transformation within Satpol PP and can serve as a model for internal e-Government implementation in managing regulatory enforcement data at the regional government level.